Pengaruh Informasi dan Tindakan Pemberian Kompres Aloevera Terhadap Penurunan Suhu Tubuh pada Anak yang Mengalami Demam di Puskesmas Nassau Kecamatan Nassau Kabupaten Toba Tahun 2024 - Siti Nurbaya; Kamelia Sinaga; Rolasnih Lilista Simbolon; Asnita Sinaga (PPNI UNIMMAN, 2024)
Background The World Health Organization (WHO) estimates that the number of fever cases in children reaches 62%. Management of fever can be in the form of non-pharmacological therapy. One non-pharmacological therapy for fever is to apply a compress using aloe vera. Aloe vera contains lignin and saponin which can vasodilate the skin and reduce body temperature. The aim of this research is to determine the effect of information and actions on giving aloe vera compresses on reducing body temperature in children with fever at the Nassau Kec.Nassau Kab.Toba Tahun 2024. This research is a type of quantitative research with a quasi-experimental research design with a pre-test and post-test design without control with subjects of 30 children aged 3 – 6 years who had a fever at the nassau public health center,nasaau district,toba regency in 2024. Community Health Center. The sampling technique in this research is total sampling, namely a sampling technique when all members of the population are used as samples. The intervention carried out was applying compressaloe vera to the forehead for 15 minutes. Temperature measurement using a digital thermometer. The data analysis used is univariate and bivariate analysis. The test used is the non-parametric Wilcoxon test. The results of this research, namely the results of statistical tests using the Wilcoxon test stated that giving aloe vera compresses had an effect on changes in body temperature in fever sufferers with a p value = 0.002 (α < 0.005) with a temperature decrease of 0.486 ºC. The conclusion of this study is that there is a significant influence on the results of measuring body temperature before and after giving aloe vera compresses to children who have fever at the nassau public health center,nasaau district,toba regency in 2024.